Perfection of methods of development of female component of MS hybrids of sugar beet ( Beta vulgaris L. ssp. vulgaris var.altissita Doell) - М. О. Корнєєва (Plant Varieties Studying and Protection)
Development and improvement of a female component of MS hybrids of sugar beet were carried out on the basis of the following methods: inereasing frequency of occurrence of sterility maintainers by means of preliminary saturation of the population with alleles of the x and z genes; the use, as a female form, of simple sterile hybrids from the crossing of sterile lines with unrelated O-types; and also the drawing in of complexes of valuable genes from materials of foreign origin.